Facile synthesis of silver-rich Au/Ag bimetallic nanoparticles with highly active SERS properties. (4th September 2019) - Tian, Shu; You, Wenjing; Shen, Yi; Gu, Xuefang; Ge, Ming; Ahmadi, Soha; Ahmad, Syed; Kraatz, Heinz-Bernhard
Abstract : A one-pot route to the synthesis of Au/Ag bimetallic nanoparticles with a high SERS activity for detection of proteins at low concentration. Abstract : The sensitive detection of proteins has attracted great interest in biomedical research since abnormal concentrations of certain proteins often indicate the presence of various chronic diseases. In this work, we propose an immunoassay method based on surface-enhanced Raman scattering (SERS) for the proof-of-concept determination of proteins by using Atto-610 labeled Au/Ag bimetallic nanoparticles (BNPs) as nanotags and a Au/Ag bimetallic film as a substrate. Without the need for added surfactants or organic precursors during the preparation process, silver-enriched Au/Ag BNPs are obtained with relatively clean surfaces by combining a galvanic replacement (GR) reaction with co-reduction of Ag atoms. The changes in morphology, composition and surface plasmon resonance (SPR) involved in the GR reaction are systematically characterized, and the possible mechanism is discussed. The BNPs exhibit considerable SERS activity due to the enrichment of Ag in the nanostructures. Upon the introduction of AuNPs by gold staining, a SERS-based super-sandwich structure is generated that is suitable for immunoassays. Using this approach, rabbit IgG is detected over a wide concentration range with a detection limit of 10 pg L −1 .